2015
DOI: 10.1177/0091450915569724
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Drug Policy Windows Internationally

Abstract: In this article, I compare and contrast policymaking processes in Canada and England and Wales between 1997 and the present day to provide insight into why the Canadian government approved the opening of a downtown Vancouver drug consumption room (DCR) named InSite in 2003, and why the British government has not yet done so. I also shed new light on why, since 2003, subsequent DCRs have not been opened in either Canada or England and Wales. I briefly consider future prospects for DCRs in both places. To accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Other authors applied the theoretical frameworks developed by public policy researchers. Notably, John Kingdon's theory of 'Multiple Streams' has proved useful to explain changes in illicit drug policy, such as the creation of supervised drug consumption facilities, or softening or hardening of illicit drug legislation [5,[27][28][29][30]]. Kingdon's premise is that there are three 'streams' of policy that operate relatively independently: problems (which often become visible after a 'crisis'), policies (the availability of a solution to the problem) and politics (receptive leaders and supporting public opinion).…”
Section: Existing Theories and Their Shortcomingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other authors applied the theoretical frameworks developed by public policy researchers. Notably, John Kingdon's theory of 'Multiple Streams' has proved useful to explain changes in illicit drug policy, such as the creation of supervised drug consumption facilities, or softening or hardening of illicit drug legislation [5,[27][28][29][30]]. Kingdon's premise is that there are three 'streams' of policy that operate relatively independently: problems (which often become visible after a 'crisis'), policies (the availability of a solution to the problem) and politics (receptive leaders and supporting public opinion).…”
Section: Existing Theories and Their Shortcomingsmentioning
confidence: 99%
“…While those theories have proved useful, they also have some weaknesses. Mainly, Kingdon's theory does not theorize the interactions between the three streams, and case studies have shown that the existence of already-available policy proposals and distinct policy entrepreneurs are not necessary conditions for change to happen [29][30][31][32]. Regarding the ACF, crises such as the AIDS/HIV epidemics have not always led to fundamental changes, ¶ the latter also occurring in the absence of a crisis or elections # [22].…”
Section: Existing Theories and Their Shortcomingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Terpstra and Fyfe (2014) examined macro-level police changes (structure, governance and accountability of police forces) across two nations (Scotland and the Netherlands). However, Kingdon's approach has been used in the drug policy field more broadly to examine, for example, the emergence of methamphetamine as a policy issue in Australia (Lancaster et al, 2014), cannabis policy in Canada (Hyshka, 2009) and drug consumption rooms policy in Canada, England and Wales (Hayle, 2015). By applying Kingdon's approach, these studies have illuminated the complexity of the drug policy process and the limitations of the 'evidence-based policy' paradigm in this contested policy domain.…”
Section: Introductionmentioning
confidence: 99%